The music instinct [videorecording (DVD)] : science & song - Mannes, Elena; McFerrin, Bobby; Levitin, Daniel J.; McDonald, Audra; Greene, Brian; Ma, Yo-Yo, 1955-; Sacks, Oliver, 1933-2015 (Distributed by PBS Distribution, 2009)
"[The film] provides a ground-breaking exploration into how and why the human organism is moved by the undeniable effect of music, and the deep connection between music and our bodies and brains. The program follows visionary researchers and accomplished musicians to the crossroads of science and culture in search of answers to music's deep mysteries." -- Container.